Effect of Iranian Black Tea Extract and Its Isolated Thearubigins on Intestinal Transit Time in Mice - K Jafari; Sh Gharibzadeh; M Faghihi; SM Karimian; M Hamzehloo; M Keshavarz (Journal of Kerman University of Medical Sciences, 2006)
Introduction: In this study, the effects of black tea extract of Iranian tea plant (Camellia sinensis var sinensis) and its polyphenolic pigment thearubigins were investigated on mice intestinal transit time. Method: Thearubigins were isolated by liquid-liquid fraction method. The effects of black tea extract and isolated thearubigins on intestinal propulsion were measured by charcoal propulsion test. Results: According to the obtained results, black tea extract increases intestinal motility and conesquently reduces transit time in a concentration dependent manner (P<0.01). Thearubigins, also, increase intestinal motility and decrease transit time dose dependently (P<0.01). Conclusion: Based upon these results, Iranian black tea extract and its major polyphenolic pigment, thearubigins, could be useful in the treatment of some gastrointestinal motility disorders.